2011
DOI: 10.1002/aic.12298
|View full text |Cite
|
Sign up to set email alerts
|

Permeation properties of hydrogen and water vapor through porous silica membranes at high temperatures

Abstract: Silica and cobalt-doped silica membranes that showed a high permeance of 1.8 Â 10 À7 mol m À2 s À1 Pa À1 and a H 2 /N 2 permeance ratio of $730, with excellent hydrothermal stability under steam pressure of 300 kPa, were successfully prepared. The permeation mechanism of gas molecules, focusing particularly on hydrogen and water vapor, was investigated in the 300-500 C range and is discussed based on the activation energy of permeation and the selectivity of gaseous molecules. The activation energy of H 2 perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
72
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 106 publications
(77 citation statements)
references
References 49 publications
1
72
3
Order By: Relevance
“…This result suggested that the Co doped into the silica existed as not only Co3O4 crystalline powder, but also as noncrystalline compounds, such as extremely fine particles that are undetectable by XRD or as Co composites with silica. XRD peaks of Co-doped silica powders fired at 19) in air, and at 600 in steamed air, had approximately the same peak intensities, suggesting that Codoped silica had good hydrothermal stability. The effect of Co composition on XRD pattern revealed that the Co3O4 peak intensities increased with the Co content in the range of from 0 to 30 Co mol%; at Co atomic composition greater than 30 mol%, the peak intensity remained relatively constant.…”
Section: Fabrication and Characterization Of Metal Doped Sio2 Membmentioning
confidence: 66%
See 4 more Smart Citations
“…This result suggested that the Co doped into the silica existed as not only Co3O4 crystalline powder, but also as noncrystalline compounds, such as extremely fine particles that are undetectable by XRD or as Co composites with silica. XRD peaks of Co-doped silica powders fired at 19) in air, and at 600 in steamed air, had approximately the same peak intensities, suggesting that Codoped silica had good hydrothermal stability. The effect of Co composition on XRD pattern revealed that the Co3O4 peak intensities increased with the Co content in the range of from 0 to 30 Co mol%; at Co atomic composition greater than 30 mol%, the peak intensity remained relatively constant.…”
Section: Fabrication and Characterization Of Metal Doped Sio2 Membmentioning
confidence: 66%
“…Figure 5 shows the TEM cross-sectional image of the top layer with 10 μm depth of a Co-doped silica membrane, which was observed using a TOPCON (Model EM002b, Tokyo, Japan) 19) . The sample was prepared using a focused ion beam (FIB) and tungsten was deposited on the surface of the top layer.…”
Section: Fabrication and Characterization Of Metal Doped Sio2 Membmentioning
confidence: 99%
See 3 more Smart Citations